The Importance Of E-Commerce, Financial Technology, And Financial Performance For MSMEs Business Sustainability - Nadila Maharani Putri; Diah Hari Suryaningrum (UNIVED Press, 2025)
This research investigates how e-commerce, financial technology, and financial performance impact the sustainability of MSMEs businesses in Banyuwangi District East Jawa, Indonesia. Employing a quantitative approach, the study utilizes primary data collected through a questionnaire. The target population comprises 297,706 MSMEs in Banyuwangi District East Jawa, Indonesia. A purposive sampling method was used to select 140 respondents. Data analysis was conducted using SEM-PLS with SmartPLS software version 4.0. The findings reveal that e-commerce significantly influences the sustainability of businesses. Financial technology affects business sustainability. Financial performance affects business sustainability. The implication is that there is a need to hold programs that encourage MSMEs to use e-commerce and financial technology to support sustainable economic growth while strengthening the business sustainability of MSMEs.